Macroeconomic determinants of Port and Douro wine exports: An econometric approach - Anthony Macedo; Sofia Gouveia; Jo\~ao Rebelo (REGION, 2020)
This study analyses recent trends (2006-2018) in Port and Douro wine exports and estimates their macroeconomic determinants. The results of the gravity equation reveal that the purchasing power in importing countries is the most important export determinant of Port and Douro wines. Therefore, in order to increase exports, the strategic decision-makers concerned with the industry should pay special attention to the markets in wealthier countries or with a high potential for economic growth, taking into account issues such as market access, adaptation to the market to wine consumption, and regulation.
Keywords: 330; International trade; Gravity model; Poisson pseudo-maximum likelihood; Wine; Demarcated Douro region